Interaksi Lama Fermentasi dan Waktu Roasting Terhadap Sifat Kimiawi Kopi Bubuk - Irwan Deo Alzidan; Muh. Aniar Hari Swasono (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The quality of the coffee fermentation and roasting process is the main factor that influences the taste and aroma of the coffee produced. Some common problems that often arise include incorrect fermentation times and over-roasting or under-roasting. Therefore, monitoring the correct fermentation and roasting times is important to pay attention to, because inappropriate fermentation and roasting times can reduce the quality of the coffee beans produced. The aim of the research is to determine the interaction between fermentation time and roasting time on the physicochemical properties of ground coffee. This research used a randomized block design (RAK) with two main factors in this research, namely the first factor was fermentation time (F) with 3 levels of fermentation time (12 hours, 24 hours and 36 hours) and the second factor was roasting time ( R) with 3 levels of roasting time (10 minutes, 15 minutes and 20 minutes). And it will be repeated 2 times, so there are a total of 18 combination treatments. The analysis carried out is physicochemical analysis including water content, ash content, caffeine content, and organoleptic analysis including color, aroma and taste. The best result is F2R3 (Fermentation 24 hours Roasting 20 minutes) including water content 2.83%, ash content 5.00%, caffeine content 0.19%, color 4.2 (like), aroma 4.00 (like), and taste 4.12 (like).